Effect of Cr and W on microstructure and wear resistance of arc additive manufactured flux-cored wire for railway wheels - Tianli Zhang; Kaiqin Yang; Zhiming Zhu; Lianyong Xu; Geng Chen; Naiwen Fang; Sindo Kou (Journal of Materials Research and Technology, 2024)
In this paper, Fe–Cr–C–W surfacing alloys was prepared by adopting arc additive surfacing technology with optimized Cr and W contents in flux-cored wire. The microstructure, hard phase, hardness and wear resistance of surfacing alloys was investigated by optical microscopy, electron microscopy, hardness and wear testing. The results show that with the increase of Cr and W, microstructure of the surfacing alloys changes from full ferrite to martensite, ferrite, retained austenite, carbides and other multiphase such as (Cr, Fe)7C3, WC and Fe2W, etc. The damage behavior gradually changes from severe abrasive wear to abrasive wear and a small amount of adhesive wear. Cr and W can significantly improve the hardness and wear resistance of the surfacing alloys. The surfacing alloys of arc additive manufactured by D4 wire with 5.91% Cr and 0.85%W exhibits good performance with a hardness of 37.9HRC and a wear amount of 0.0011g, which meets the requirements of railway wheels.